N-TERMINAL BRAIN NATRIURETIC PROPEPTIDE AS A MARKER OF MULTIFOCAL ATHEROSCLEROSIS IN PATIENTS WITH ST SEGMENT ELEVATION MYOCARDIAL INFARCTION - O. L. Barbarash; E. N. Usoltseva; K. S. Shafranskaya; M. V. Zykov; O. V. Gruzdeva; O. M. Polikutina; V. V. Kashtalap (Российский кардиологический журнал)
Aim. To investigate the association between serum levels of N‑terminal brain natriuretic propeptide(Nt-proBNP)andtheseverityofcoronaryandnon-coronaryatherosclerosisin patients with myocardial infarction and ST segment elevation (STEMI). Material and methods. The study included 186 STEMI patients. All participants underwent coronary angiography and angioplasty with infarct-related artery stenting, as well as the screening assessment of non-coronary atherosclerosis of brachiocephalic arteries and large lower extremity arteries. The measurement of Nt-proBNP levels was performed 10–14 days after the STEMI onset. Results. Nt-proBNP levels were not associated with the severity of coronary atherosclerosis. However, patients with more advanced non-coronary atherosclerosis and a higher number of affected non-coronary vessels demonstrated elevated Nt-proBNP concentrations. After adjustment for age, severity of heart failure and myocardial dysfunction, Nt-proBNP were still associated with atherosclerosis multifocality. Conclusion. In STEMI patients, Nt-proBNP concentrations were associated with severity and multifocality of non-coronary atherosclerosis. This could be used in clinical practice for predicting the risk of repeat atherosclerotic cardiovascular events.